Perancangan dan Penerapan Algoritme 4DES (Studi Kasus Pada Keamanan Berkas Rekam Medis) - Yeni Yanti; Teuku Yuliar Arif; Rizal Munadi (Universitas Syiah Kuala, 2016)
Information is necessary for life because everything can not be done properly in the absence of information. The security problem is one of the most crucial aspects of a file containing sensitive information, for example, medical record files. Often, the file owner, designer, and manager of the information systems pay less attention to the security issues. One way to anticipate this is by using a cryptographic method, which is the science and art to keep the message security. This study aimed to evaluate the performance analysis and building a security system prototype of medical record files using the 4DES algorithm. The 4DES algorithm is a variant of the 3DES algorithm that is more robust and capable of protecting information properly. The 4DES security system has four keys; each key has a key length of 64 bits so that the total length of four keys is 256 bits and K1≠K2≠K3≠K4. The encrypted / decrypted files (Word, Excel, and Image) using an external key of minimum eight characters (64 bits). During encryption, there was an addition of padding bytes in each of data block size to minimalized attack from the attacker using a CBC operation mode process. Results showed that the processing speed of the encrypted files using the 4DES was 1 second faster than that of using the 3DES algorithm. Also, the 4DES algorithm has superiority regarding of file safety, which has time enduring 3.45 x1056years longer to brute force attack technique which able to discover text file and the secret key.